2007
DOI: 10.1093/ps/86.9.1904
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Bacteriophages Isolated from Different Sources to Reduce Salmonella enterica Serovar Enteritidis In Vitro and In Vivo

Abstract: Salmonella enterica serovar Enteritidis-lysing bacteriophages isolated from poultry or human sewage sources were used to reduce Salmonella Enteritidis in vitro and in experimentally infected chicks. Cocktails of 4 different bacteriophages obtained from commercial broiler houses (CB4Ø) and 45 bacteriophages from a municipal wastewater treatment plant (WT45Ø) were evaluated. In experiment 1, an in vitro crop assay was conducted with selected bacteriophage concentrations (10(5) to 10(9) pfu/mL) to determine abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(60 citation statements)
references
References 26 publications
4
49
0
2
Order By: Relevance
“…Moreover, bacteriophages have previously been used to control intracellular pathogens [27]. Some bacteriophages can be efficacious in reducing S. enteritidis colonization in poultry during a short period [18]. In our study, we were able to clear Salmonella from infected chicks after successive phage treatments applied within a short time period after infection.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Moreover, bacteriophages have previously been used to control intracellular pathogens [27]. Some bacteriophages can be efficacious in reducing S. enteritidis colonization in poultry during a short period [18]. In our study, we were able to clear Salmonella from infected chicks after successive phage treatments applied within a short time period after infection.…”
Section: Discussionmentioning
confidence: 60%
“…Presence of Salmonella specific bacteriophages has previously been reported from excretion sewage of commercial broiler houses [24]. Meanwhile Andreatti Filho et al [18], isolated bacteriopgages from environmental drag swabs in commercial broiler houses. Spot tests were used in this study to confirm the presence of specific bacteriophages in the preparations, other studies such as Rahaman et al [17], have used similar strategies to test for the presence of specific bacteriophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phages have also been applied on meat as well as fruits (Leverentz et al 2001) and vegetables (Viazis et al 2011) to control pathogens. They have successfully controlled bacterial infections caused by different kinds of bacteria, like Salmonella (Andreatti Filho et al 2007), Pseudomonas aeruginosa (McVay et al 2007), Staphylococcus aureus (Wills et al 2005), Clostridium difficile (Ramesh et al 1999), Escherichia coli (Huff et al 2002), and Campylobacter (Loc Carrillo et al 2005) in large animals and poultry. They significantly reduced Salmonella enterica colonization and horizontal transmission (Lim et al 2012).…”
Section: Nonclinical Applicationsmentioning
confidence: 99%
“…Thus, phage therapy has been proposed as a means to control Salmonella infection in chickens. Indeed, several studies have shown that phages effectively reduce Salmonella enterica colonization in poultry (11)(12)(13)(14)(15). The utility of phages in food preservation and safety has also been demonstrated (16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%